ปัจจัยที่ส่งผลต่อการเลือกอาชีพนักวิทยาศาสตร์ของนักเรียนมัธยมศึกษาตอนปลาย - ศุภมาส เจือกโว้น (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this research was to study the factors affecting the decision making of upper secondary school students to choose scientist careers. The research sample consisted of 452 students. The research instrument employed was a questionnaire concerning the relevant factors. The model consisted of 1 dependent variable and 10 independent variables. The data were analyzed by using the principle of LISREL model analysis, using LISREL program version 8.72. The major findings were as follows: 1.The model of factors affecting the decision making of upper secondary school students in choosing scientist careers was valid and fit the empirical data with X² = 0.00 , p = 1.00, df = 0 and RMSEA = 0.00. The model accounted for 42% of variance in the decision making. 2.The decision making by upper secondary school students in choosing scientist careers received the maximum effect from the interest variable, followed by the model variable, ability variable, current variable and salary variable, respectively.